Comparison Between Conventional and Vegetated Roof by Means of a Dynamic Simulation. (November 2015) - Ferrante, Patrizia; La Gennusa, Maria; Peri, Giorgia; Scaccianoce, Gianluca; Sorrentino, Giancarlo
Abstract: In this paper, a dynamic simulation of a building located in the Campus University of Palermo, Italy, has been carried out. We considered two different scenarios; in the first one, the building as it is, with a conventional covering, while in the second one the roof was equipped with a green roof. The results of the two simulations have been compared, suggesting that such building component could contribute to the energy savings of the building. However, it has to be considered as part of other possible actions devoted to improve the energy efficiency of the whole building.